The world of plant and animal communities - Miller, Sue (Chicago : Encyclopaedia Britannica Educational Corporation, 1981)
In defining the term'community' for young viewers, shows how all living things depend on one another for food and shelter. Closeup photography invites viewrs to explore several different types of communities, such as forest, desert, ocean, and grassland
Keywords: Biotic communities -- Juvinile films; Biotic communities